The prevalence of major mental illness, substance misuse and homelessness in Irish prisoners: systematic review and meta-analyses. (9th May 2018) - Gulati, G.; Keating, N.; O'Neill, A.; Delaunois, I.; Meagher, D.; Dunne, C. P.
Abstract : Aims: To systematically review studies from Irish prisons that estimate the prevalence of major mental illness, alcohol and substance misuse, and homelessness at the time of committal. Methods: Healthcare databases were searched for studies quantifying the point prevalence for each outcome of interest. Searches were augmented by scanning of bibliographies and searches of governmental and non-governmental websites. Proportional meta-analyses were completed for each outcome. Results: We found eight, six and five studies quantifying the point prevalence of major mental illness, substance misuse, and homelessness respectively. Considerable heterogeneity was found for each subgroup (except psychosis where substantial heterogeneity was observed) and random effects models were used to calculate pooled percentages. The pooled percentage for psychotic disorder was 3.6% [95% confidence interval (CI) 3.0–4.2%], for affective disorder 4.3% (95% CI 2.1–7.1%), for alcohol use disorder 28.3% (95% CI 19.9–37.4%), for substance use disorder 50.9% (95% CI 37.6–64.2%) and for those who were homeless on committal 17.4% (95% CI 8.7–28.4%). Conclusions: Estimates for the prevalence of psychotic illness and substance abuse amongst Irish prisoners are in keeping with international estimates of morbidity in prisons, whilst those for affective disorders are lower. The prevalence of homelessness in committal to Irish prisons is higher than some international estimates. Rates for psychoses, alcohol and substance misuse as well as homelessness in Irish prisons are significantly higher than the general population prevalence of these vulnerabilities. A need for service development is discussed.